Identification and Enumeration of Pathological Organisms in Krishnagiri Reservoir, Krishnagiri District, Tamil Nadu, India - Prabhahar, C (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT In this present study, hydro biological characteristic features of the Krishnagiri reservoir Dam were investigated. The data for the present study were collected from 3 sampling stations for the period of 6 months in both premonsoon and monsoon seasons. Ten bacterial isolates were identified in different study area. The present study was aimed to enumerate the total Escherichia coli, faecal coliforms, Pseudomonas sp., Aerobacter sp., Clostridium sp., Shigella sp., Vibrio cholerae, Vibrio parahaemolyticus, Staphylococcus sp. and yeast. All this things keeping in the mind, the present study was carried out to detect the bacterial populations.